Growth and Sporulation of Curvularia eragrostidis as Affected by Media and Nitrogen Sources - Prajapati, V. P.; Gajre, N. K.; Tandel, D. H.; Deshmukh, A. J.; Patel, R. C. (International Journal of Economic Plants, 2016)
Out of eight synthetic and semi-synthetic solid and liquid culture media tested, host leaf extract agar and potato dextrose agar were the best semi-synthetic media for the growth of the Curvularia eragrostidis. Among liquid media, oat meal broth, potato dextrose broth and Richards’ broth medium were best for the growth and sporulation of C. eragrostidis, while nitrogenous sources tried asparagine, L-glutamic acid, ammonium nitrate, potassium nitrate, ammonium sulphate and calcium nitrate proved to be the best for the growth and sporulation of the pathogen. Sodium nitrate and urea showed poor growth and sporulation of the C. eragrostidis.